It's halloween, you 'fraidy mouse! / merry christmas, geronimo! eaudiobook - Stilton, Geronimo (Geronimo Stilton, 2017)
Spend the holidays on Mouse Island. Celebrate Halloween and Christmas with the bestselling mouse detective.